Effective Management to Support Tahfidz Al-Qur’ān Course in Indonesian Islamic Higher Education - Nasrulloh; Hamim Syaiful Rijal; Wirayudha Mahendra; Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
The purpose of this study is (was) to determine the management of the tahfidz al-Qur’ān course at UIN Sunan Kalijaga Yogyakarta and UIN Malang and to find out the factors that influence the differences between the two and their relevance in the development of tahfidz al-Qur’ān courses in the two universities. This type of research was included into the empirical-qualitative category using Miles and Huberman-style analysis. The data collection was taken from interviews, observations and documentation. The standards of the management theory as the reference were the five principles set by Fayol. The results of this study present that the management of the tahfidz al-Qur’an course at UIN Sunan Kalijaga Yogyakarta and UIN Malang had several similarities and differences in terms of planning. Each lecturer provided the explanations related to targets and memorization and memorization deposit mechanisms. The differences from the two were only the methods and targets set. As for the Organizing, Commanding, Coordinating and Controlling sides, it was broadly the same. What distinguished was only the technical implementation. The factors that influenced the existence of differences in the management of the the tahfidz al-Qur’an course were the absence of standard provisions and rules on the methods in teaching tahfidz al-Qur’an courses between the two universities. Tahfidz course management has relevance to the development into the Department of Qur’anic Studies matters in terms of graduate achievement and competence. This research gives a message that the lecturers of tahfidz courses have to make special strategies that can be applied uniformly by every tahfidz course supervisor in higher education.